新加坡道教斋醮功能性研究 = A study on functionality of Singapore taoist ritual : observations from Jin Fu Gong Temple and Nanyang Neo Clan “Qing Jiao” rituals - 梁伟利 Liang, Weili (2011)
作为中国本土的宗教，道教可算是承载了一部分中华文化。而“斋醮”是中国古代祭祀仪式的代表，是受社会各个阶层所重视的。道教在汉朝建教以后，斋醮就纳入了道教重要的科仪。斋醮流传至现今的社会已经有了上千年的历史。能做到这点，主要原因在于斋醮有着符合社会需求的功能性。新加坡是个多元宗族与宗教的移民社会。道教流传到新加坡的历史可以追溯至开埠前，十八世纪末。而斋醮也以简单的形式在新加坡慢慢盛行起来。新加坡道教的发展一路走来都相当的不平坦，多年来受到不少的限制。虽然目前正式信奉道教的人士只有少过占总人口的百分之十，但新加坡独有的“斋醮文化”却仍受到多数华族人民的重视。本地的斋醮仪式分除了有为阴界超度的小型“斋醮”仪式，另外还分别有为神明圣诞祝寿以及为善信消灾祈福两种较为大型的“清醮”仪式，体现的是斋醮在新世纪的多元性功能。As a lay religion of China, Taoism is said to succeed a portion of Chinese culture. “Zhai Jiao” is a representation of ancient ceremonial rituals of China and attracts much attention by people from different levels in society. “Zhai Jiao” has been incorporated in Taoist ceremonies ever since the Han Dynasty, creating a history of more than a millennium. The reason why “Zhai Jiao” is still emphasized today is due to its functionality is society. Singapore is a multi-religious society, encompassing a big portion of immigrants. The history of Taoism in Singapore can be traced till the late eighteenth century, before her development. “Zhai Jiao” has also gradually became popular as customaries are being simplify. However, the development of Taoism in Singapore faced many restrictions and was never smooth-sailing. Though less than ten percent of the population are Taoists, the culture of “Zhai Jiao” is still respected by the Chinese community.